2015
DOI: 10.1186/s12885-015-1104-5
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the impact of platinum dose reduction and chemotherapy delays on the outcomes of stage III ovarian cancer patients

Abstract: Background: Ovarian cancer is a common gynaecological malignancy still remaining a challenge to treat. The objective of this study was to evaluate the impact of platinum dose reduction and chemotherapy delays on progression free survival and overall survival in patients with stage III ovarian cancer and to analyze reasons for such chemotherapy scheme modifications. Methods: Medical records of patients with FIGO stage III ovarian cancer were reviewed. Inclusion criteria involved FIGO stage III epithelial ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
4
19
0
2
Order By: Relevance
“…The average age of patients exhibiting ovarian cancer was 58.6 years (range, 40–85 years) and all diagnoses were confirmed via pathological examination. Tumor staging was performed according to the International Federation of Gynecology and Obstetrics (FIGO) criteria (2010) ( 21 ). In addition, samples from 29 healthy women served as the control group, and the average age of these patients was 57.7 years (range, 42–75 years).…”
Section: Methodsmentioning
confidence: 99%
“…The average age of patients exhibiting ovarian cancer was 58.6 years (range, 40–85 years) and all diagnoses were confirmed via pathological examination. Tumor staging was performed according to the International Federation of Gynecology and Obstetrics (FIGO) criteria (2010) ( 21 ). In addition, samples from 29 healthy women served as the control group, and the average age of these patients was 57.7 years (range, 42–75 years).…”
Section: Methodsmentioning
confidence: 99%
“…Retrospective study involving 1243 centres in USA of prevalence and reasons for dose adjustment of early stage breast cancer adjuvant chemotherapy showed that dose reductions ≥15% occurred in 36.5% of patients, and there were treatment delays ≥7 days in 24.9% of patients, resulting in 55.5% of patients receiving RDI less than 85% [ 2 ]. Clinical studies show that dose reduction and chemotherapy delay in treatment of chemotherapy sensitive tumours – non-Hodgkin lymphoma [ 3 , 4 ], early stage breast cancer [ 5 ], advanced ovarian cancer [ 6 ] – are related to lower survival rates. Later clinical studies proved negative prognostic effect of reduced planned dose of chemotherapy for early stage breast cancer on patients’ survival [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact role of RDI in veterinary medicine is unclear. Even in human oncology, RDI may have different impacts across tumor types, 49 and possible artifacts might complicate its interpretation. 50 Most chemotherapy dosages are based on the patient's body surface area, which does not correlate well with drug pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%